Konseling gizi dan pengaruhnya terhadap asupan zat gizi dan tekanan darah pada pasien hipertensi rawat jalan di Rumah Sakit Umum Daerah Provinsi Sulawesi Tenggara - Suwarni Suwarni; Ahmad Husein Asdie; Herni Astuti (Jurnal Gizi Klinik Indonesia, 2009)
Background : Hypertension is one of the most common worldwide diseases that can be an important public health challenge. The causes of hypertension are high consumption of salt and fat, obesity, stress, age, sex, family history, smoking, and consumption of alcoholic drinks. The prevalence of hypertension in the world, Asia, and Indonesia are 15-20%, 8-18%, and 1,8-28,6%, respectively. The solution to this problem is not only depend on drugs but also counseling through leaflet as the process of assisting clients in facing the problem of hypertension.Objectives : To know the effect of nutrition counseling on nutrition intake and blood pressure of hypertension outpatients at local hospital of the Province of Southeast Sulawesi. Methods : The study was quasi experimental with pre- and post-control design. Samples were divided into 2 groups; intervention group was given nutrition counseling and leaflet and the second (control) was only given leaflet. Samples were hypertension outpatients who fulfilled inclusions and exclusions criteria, and there were 25 samples per group. Data of nutrient intake were processed using Nutrisurvey. Chi-square test was used to identify the difference between the intervention group and the control group; whereas t-test was used to identify independent as well as dependent variables.Results : There were no significant differences in intake of fat, natrium, potassium, and magnesium between the intervention group and control group (p > 0.05); but there were differences between them at the end of study (p < 0.05). Blood pressures of both of them were also not different (p > 0.05); however, at the end of study there was difference between them (p < 0.05).Conclusion : Nutrition counseling could improve nutrition intake and blood pressure of hypertension outpatients at local hospital of the Province of Southeast Sulawesi.